Modern algebra and trigonometry - Robinson, J. Vincent (New York : McGraw-Hill Book Company, 1966)
The primary aim of this book is to provide a suitable foundations for modern courses in analytic geometry and calculus.
Chapter 1. Real numbers -- Chapter 2. First-degree equations -- Chapter 3. Functions and graphs -- Chapter 4. Trigonometric functions -- Chapter 5. Factoring polynomials, operations with fractions -- Chapter 6. Exponents, exponential functions.
Includes bibliographical references and index.
Keywords: GEOMETRY; CALCULUS